2019
DOI: 10.1016/j.ajhg.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Mutations in TTC21A Induce Asthenoteratospermia in Humans and Mice

Abstract: Male infertility is a major concern affecting human reproductive health. Asthenoteratospermia can cause male infertility through reduced motility and abnormal morphology of spermatozoa. Several genes, including DNAH1 and some CFAP family members, are involved in multiple morphological abnormalities of the sperm flagella (MMAF). However, these known genes only account for approximately 60% of human MMAF cases. Here, we conducted further genetic analyses by using whole-exome sequencing in a cohort of 65 Han Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 36 publications
0
97
0
1
Order By: Relevance
“…The genetic characterization of this phenotype began in 2014 with the identification of DNAH1 (dynein axonemal heavy chain 1) as a major gene implicated in MMAF . After the development and the introduction of high throughput sequencing (HTS) techniques such as whole exome sequencing (WES), deleterious mutations were formally identified in eight additional MMAF genes ( AK7 , ARMC2 , CFAP43 , CFAP44 , CFAP69 , FSIP2 , TTC21A , and WDR66 ) showing the high genetic heterogeneity of this phenotype. Despite these important advances in gene identification, about half of the MMAF cases remain idiopathic without a genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic characterization of this phenotype began in 2014 with the identification of DNAH1 (dynein axonemal heavy chain 1) as a major gene implicated in MMAF . After the development and the introduction of high throughput sequencing (HTS) techniques such as whole exome sequencing (WES), deleterious mutations were formally identified in eight additional MMAF genes ( AK7 , ARMC2 , CFAP43 , CFAP44 , CFAP69 , FSIP2 , TTC21A , and WDR66 ) showing the high genetic heterogeneity of this phenotype. Despite these important advances in gene identification, about half of the MMAF cases remain idiopathic without a genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, when MMAF was defined, studies have shown that mutations in genes associated with sperm flagellum development may lead to MMAF . Here, another candidate gene, CFAP65 , was identified in an infertile male with MMAF by WES.…”
Section: Discussionmentioning
confidence: 95%
“…The genetic basis of male infertility is still a work in progress, more than 4000 genes are expressed in germ cells during sperm production, and variations in these genes may hamper spermatogenesis . Recent studies of families with positive history related to male infertility have reported that mutations in cilia‐related genes are responsible for MMAF (eg, DNAH1 , CFAP43 , CFAP44 , CFAP69 , CFAP251 , QRICH2 , AK7 , CEP135 , FSIP2 , SPEF2 , TTC21A , ARMC2 , AKAP4 , CCDC39 ) . However, the known genetic defects can only explain ~60% of the individuals affected by MMAF …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations